Morfologia del sistema digestivo de Hypothenemus hampei (Ferrari) - Rubio G, J.D.=700 1 Bustillo P, A.E.; Vallejo E, L.F.; Benavides M, P.; Acuña Z, J.R.
(En, Es)
ilus., 18 ref.
Keywords: HYPOTHENEMUS HAMPEI; ANATOMIA ANIMAL; SISTEMA DIGESTIVO; COLOMBIA; BROCA DEL CAFE; CENICAFE